A B-spline design model for propeller blades. (April 2018) - Pérez-Arribas, F.; Pérez-Fernández, R.
Highlights: This work presents a new design methodology for modelling the blades of propellers using B-spline surfaces. Propeller blades are good examples of free form surfaces, designed specifically considering several parameters that control their performance. .Traditional tools for surface design in CAD, control point manipulation, are not appropriated for blade design, since geometric parameters are used Commondesign parameters for the geometry of propellers are used and a final B-splinesurface for the geometry of the blades is produced The methodology can be converted for turbo-macCommon design parameters for the geometry of propellers are used and a final B-spline surface for the geometry of the blades is producedhinery components by changing the stream surfaces (cylinders in the case of propellers) to others Abstract: This work presents a new design methodology for modelling the blades of propellers using B-spline surfaces. Propeller blades are good examples of free form surfaces, designed specifically considering several parameters that control their performance. Traditional tools for surface design in CAD, such as control point manipulation, are not appropriated for blade design, and the designers prefer to work with design parameters that possess a clear aerodynamic / hydrodynamic meaning. This method uses common design parameters for the geometry of propellers and produces a final B-spline surface for the geometry of the blades that can be used for the visualisation, calculations, and construction of the propeller. The method starts with the definition of a 3D grid of points that form the propeller blades based on the 2D definition of a series of cross-sectional profiles at several radial locations. Propeller blades are very thin objects with great changes of curvature, and if standard B-spline techniques are used, they cannot be modelled well under a tolerance unless a large number of control points is used, producing very complex surfaces. The inclination and twist of the blades are given by rake and pitch angles, quite common in the design procedures. The method stresses the fitting of the blade's leading edge which has great effect on the propeller behaviour and geometrically has a small curvature radius in comparison with the rest of the blades.